P112 Deeper phenotyping of non CF bronchiectasis through sputum differential counts. (14th November 2013) - Davison, J; Johnson, G; Jiwa, K; Cranson, A; Wake, R; Hood, B; Small, T; Birch, J; Fisher, A; De Soyza, A
Abstract : Introduction and Objectives: Non CF Bronchiectasis has diverse aetiologies. This includes idiopathic, systemic disease related and as a complication of asthma. Such diversity may be important in determining therapeutic strategies (personalised medicines) and may also be an important consideration in clinical trial design. This is increasingly relevant when neutrophil targeting or eosinophil targeted therapies are being developed. We hypothesised that patients could be phenotyped by sputum cytospins irrespective of suspected aetiology or disease severity. Methods: Patients underwent a standardised clinical phenotyping protocol including HRCT chest (Anwar et al 2013). Baseline therapy was recorded. Spontaneous sputa were collected in stable state and spirometry was undertaken according to guidelines. Sputum cell counts were calculated using standard methods with data expressed as medians and ranges. Results: Fifty three patients' data are reported. The M:F ratio was 1:1.4. The mean FEV1 predicted was 62%, mean FEV1/VC ratio was 64%. Forty three (83%) were on inhaled corticosteroids and 24.5% had a historical diagnosis of asthma and /or ABPA. The predominant cell in sputa was neutrophils, median 94 (range 23–100%), macrophages were the 2nd most prevalent cell type median 2.6 (range 0–75%). Eosinophils showed a skewed distribution with median of 0.2 with a range of 0–24.8%. Four patients had sputum eosinophilia >3%. Of these, only 2 had a history of asthma and / or ABPA being diagnosed. Despite historical diagnoses of asthma and / or ABPA in 13 patients the eosinophil percentage was not statistically different to "non asthmatics". (P = 0.59 Chi Sq test) This group included features of ABPA in 2 patients and significant atopy in another. Conclusions: Non CF bronchiectasis patients usually have sputum neutrophil dominance. Sputum eosinophilia is rare (<10% of patients); however such patients may need alternative therapeutic strategies. Excluding bronchiectasis patients with a history of asthma from trials targeting neutrophils seems unnecessary. The neutrophilic predominant profiles in asthmatic bronchiectasis patients suggest either asthma misdiagnosis or that neutrophil predominant asthmatics may be more susceptible to developing bronchiectasis. Longitudinal studies are needed to determine if the sputum cell profiles are static in stable patients. These data may help develop a more personalised medicine approach in bronchiectasis. References: Anwar GA, et al. 2013 Phenotyping adults with non-cystic fibrosis bronchiectasis: A prospective observational cohort study. Respir Med . Jul;107(7):1001–7. doi: 10.1016/j.rmed.2013.04.013. Epub 2013 May 11.